Pandemic Pedagogy: Elements of Online Supportive Course Design - Nate S. Brophy; Melissa Broeckelman-Post; Karin Nordin; Angela D. Miller; Michelle M. Buehl; Jeff Vomund (Central States Communication Association, 2021)
The purpose of this study was to identify which course design elements students perceive as supporting an easier transition to emergency remote teaching due to COVID-19, as well as to use those items to develop the Online Supportive Course Design (OSCD) measure. By asking students to rate their course with the easiest transition and hardest transition to emergency remote teaching, this study identified which structural elements were most important for supporting students during the transition. Using exploratory and confirmatory factor analyses, a seven-item measure was developed to operationalize OSCD, and initial validity was established by examining the relationships between OSCD, autonomy support, and teacher competence. Finally, practical implications for university faculty and areas for future research are discussed.